Green choices matter: Linking environmental concern and environmental knowledge to green purchase intention via customer attitude - Ikhwan Mubaroq; Fauza Rahmadani (Journal of Management and Business Insight, 2025)
Purpose-Increased attention to environmental issues has encouraged changes in consumer behavior in choosing more environmentally friendly products. However, green purchase intention is not only influenced by concern for the environment, but also by consumers' level of knowledge and their attitudes toward environmentally friendly products. This study aims to determine the influence of environmental concern and environmental knowledge on green purchase intention through customer attitude as a mediating variable. Methodology-The population in this study consists of Avoskin consumers in Indonesia, with a sample size of 120 respondents. The study used purposive sampling with several conditions. Data was collected by distributing questionnaires online. This study used Smart PLS 4.0 software to test the validity, reliability, and hypotheses of the research data. Findings-This study proves that environmental concern and environmental knowledge have a positive effect on green purchase intention and customer attitude. Customer attitude has a positive effect on green purchase intention. Furthermore, customer attitude partially mediates the positive effect of environmental concern and environmental knowledge on green purchase intention. Research Limitations-This study has limitations in terms of the number of respondents and the context of the research, which was conducted only on Avoskin consumers in Indonesia. Generalization of the findings to other skincare brands still needs to be further examined. Furthermore, this study only measures green purchase intention and does not observe actual green purchasing behavior of consumers. Novelty-This study offers novelty by positioning customer attitude as the main psychological mechanism that bridges the influence of environmental concern and environmental knowledge on green purchase intention within the integrative framework of the Theory of Planned Behavior and Knowledge-Based View. The novelty of this study also lies in its application to local skincare brands in Indonesia, which have been relatively understudied in the green purchase intention literature.